PENYALAHGUNAAN KARTU KREDIT PEMBELI VOUCHER GAME ONLINE MELALUI E-COMMERCE - Paxsi Erlangga, Brillyan Bagas (Journal of Private and Economic Law, 2023)
Online buying and selling is part of the trade of online games. The case discussed here involves the misuse of a credit card by a buyer of online game vouchers through e-commerce. As in the case experienced by a woman named Martin, she received a notification of a charge of 50 million Rupiah on her e-banking account. The legal fact is that Mrs. Martin’s child conducted online game voucher transactions without parental supervision, resulting in a 50 million Rupiah charge on Mrs. Martin’s credit card. Unbeknownst to the child, the online game account was directly linked to the credit card, causing a significant increase in the credit card bill. This research aims to understand the legal protection for consumers, specifically credit card users who suffer losses due to online purchase agreements conducted through electronic media (e-commerce), based on Law Number 8 of 1999 concerning Consumer Protection. In this journal, a normative legal research method is employed, utilizing theories, regulations, and other legal materials such as books, journals, and related documents. The author adopts two main approaches, namely the Statute Approach and the Conceptual Approach. The research results indicate that Microsoft explained there is still a way to resolve this issue by providing a 14-day review period for all reports that the purchase of online game vouchers was made by a minor without parental supervision. Microsoft decided to refund the money once, corresponding to the purchase of the online game voucher. Thus, in the case above, various legal actions can be pursued by credit card users who are harmed in e-commerce transactions. Following the provisions of Article 19 (3), Article 45 (1), and Article 47 of the Consumer Protection Law, consumer disputes can be resolved both out of court and through the court system. Keywords: Consumer Protection, Online Game, Purchase